Coating for building exterior wall and preparation method thereof
Through a new method of coating preparation for building exterior walls, combined with modified lithium silicate, iron oxide copper and zirconium dioxide-yttrium oxide composite microspheres, the shortcomings of existing coatings in temperature resistance, aging resistance and heat insulation properties are solved, and the excellent performance and higher usage effects of the coating are achieved.
Patent Information
- Application Number
- CN202411958830.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-21
AI Technical Summary
Existing paints for exterior walls for building have shortcomings in temperature resistance, aging resistance and heat insulation properties, and it is difficult to meet the requirements of high weather resistance and energy conservation and environmental protection.
A method for preparing coatings for building exterior walls is adopted. By mixing water and thickener, dispersing agent, defoaming agent and wetting agent, then adding modified lithium silicate, copper iron oxide and zirconium dioxide-yttrium oxide composite microspheres, combined with silicon acrylic emulsion and acrylic emulsion, pulsed magnetic field treatment is performed, and finally film forming additives, preservatives and defoaming agents are added to form coatings with excellent temperature resistance, anti-aging and heat insulation properties.
This paint has excellent performance in temperature resistance, aging resistance and thermal insulation performance, and can effectively meet the needs of building exterior walls and provide better protection and energy-saving effects.
Smart Images

Figure BDA0005216580050000101
Abstract
Description
Technical Field
[0001] The present invention relates to a coating for building exterior walls and a preparation method thereof, belonging to the technical field of building materials. Background Art
[0002] Paints for building exterior walls play a vital role in the maintenance and beautification of buildings. In recent years, with climate change and people's increasing awareness of environmental protection, people's requirements for paints for building exterior walls have become higher and higher. Compared with paints for other application environments, paints for building exterior walls are outdoors for a long time and require higher tolerance to changes in the external environment. In addition, improving the thermal insulation performance of paints is more energy-saving and environmentally friendly, which has also become one of the basic requirements for paints for building exterior walls.
[0003] Currently, the coatings with the best decorative effect and the best weather resistance are solvent-based fluorocarbon coatings. However, these coatings have significant defects in actual use, such as serious solvent pollution, high cost, and difficulty in construction. Although water-based fluorocarbon coatings are now available on the market, their cost is still very high, making it difficult to promote and apply them on a large scale.
[0004] Patent CN115895372B discloses a waterproof and heat-insulating exterior wall coating and its preparation method, which is made by mixing silicone-acrylic emulsion, fluorocarbon resin, filler, thickener, leveling agent, defoamer, film-forming mixed auxiliary agent, reflective heat-insulating powder mixture, water and the like as raw materials. The patent uses lauryl ester, dipropylene glycol butyl ether and dipropylene glycol methyl ether in a specific mass ratio as film-forming mixed auxiliary agents, and uses titanium dioxide, silicon dioxide and aluminum oxide in a specific mass ratio as reflective heat-insulating powder mixture. In the mixed system mainly composed of silicone-acrylic emulsion and fluorocarbon resin, the coating can exert excellent waterproof and heat-insulating performance, which is conducive to obtaining an exterior wall coating with excellent quality. The coating obtained by this patent technology has good rainwater erosion resistance and heat insulation performance, but the temperature change resistance and aging resistance are not ideal.
[0005] It is of great significance to improve existing coating products and comprehensively enhance their resistance to temperature changes, anti-aging and thermal insulation properties. Summary of the invention
[0006] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and to provide a coating for building exterior walls and a preparation method thereof, which has excellent temperature resistance, anti-aging and heat insulation effects.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] A method for preparing a coating for building exterior walls, in parts by weight, comprises the following specific steps:
[0009] (1) First, 10 to 12 parts of water and 0.8 to 1.5 parts of thickener are mixed and stirred, and then 1 to 2 parts of dispersant, 0.1 to 0.15 parts of defoamer and 0.4 to 0.5 parts of wetting agent are added, and stirring is continued to obtain a premix;
[0010] (2) Then, 3 to 5 parts of modified lithium silicate, 5 to 7 parts of copper iron oxide, and 3 to 4 parts of zirconium dioxide-yttrium oxide composite microspheres are added to the premix, and the mixture is evenly dispersed by stirring, and 20 to 25 parts of silicone-acrylic emulsion and 25 to 30 parts of acrylic emulsion are added, and the mixture is evenly stirred and treated with a pulsed magnetic field;
[0011] (3) Finally, add 6 to 8 parts of film-forming aid, 1 to 1.5 parts of preservative, and 0.1 to 0.15 parts of defoamer, stir and mix, add 1 to 2 parts of thickener, stir and mix, and the coating for building exterior walls is obtained.
[0012] Preferably, the thickener is selected from hydroxyethyl cellulose, hydroxymethyl cellulose or carboxymethyl cellulose; the dispersant is selected from sodium dodecylbenzene sulfonate, fatty acid sulfonamide or sodium dibutylnaphthalene sulfonate; the defoamer is a mineral oil defoamer, such as HY-A10, purchased from Shanghai Huiyan New Materials Co., Ltd.; the wetting agent is selected from glycerol or propylene glycol; the silicone acrylic emulsion is purchased from Shandong Xuguang Chemical Co., Ltd.; the acrylic emulsion is purchased from Shandong Chuangying Chemical Co., Ltd.; the film-forming aid is obtained by mixing equal masses of ethylene glycol and dodecyl alcohol; the preservative is selected from 5-chloro-2-methyl-4-isothiazoline-3-one or 1,2-benzisothiazolin-3-one.
[0013] Preferably, in step (1), the process conditions for mixing and stirring are: stirring at 300-400 r / min for 8-10 minutes; and the process conditions for continued stirring are: stirring at 300-400 r / min for 5-7 minutes.
[0014] Preferably, in step (2), the modified lithium silicate is prepared by the following method, in parts by weight: 10 parts of a 5-10% lithium silicate solution is heated to 50-60° C., 3-4 parts of 3-ureapropyltriethoxysilane are added while stirring, and then 1 mol / L lithium hydroxide solution is added to adjust the pH to 11-12, and then 1-2 parts of γ-aminopropyltriethoxysilane and 1-2 parts of methyltriethoxysilane are added, the reaction is stirred and kept warm for 2-3 hours, and the mixture is naturally cooled to room temperature to obtain the modified lithium silicate.
[0015] Preferably, in step (2), the copper iron oxide is prepared by the following method, in parts by weight: 1 part of CuO, 2 to 3 parts of Fe2O3 and 0.2 to 0.25 parts of polyvinyl pyrrolidone are mixed and ground for 2 to 3 hours, then calcined at 450 to 550° C. for 2 to 3 hours, and naturally cooled to room temperature to obtain the copper iron oxide.
[0016] Preferably, in step (2), the zirconium dioxide-yttrium oxide composite microspheres are prepared by the following method, in parts by weight: first, 2 to 3 parts of zirconium oxychloride and 1 part of yttrium nitrate are dissolved in 8 to 10 parts of water to obtain an aqueous solution; then, 4 to 5 parts of polystyrene microspheres (purchased from Beijing Zhongke Keyou Technology Co., Ltd.) and 5 to 7 parts of anhydrous ethanol are added to the aqueous solution, ultrasonically vibrated at 300 to 500 W for 10 to 15 minutes, heated to 80 to 90° C., stirred at 300 to 500 r / min for 8 to 10 hours, filtered to obtain the solid, washed with water until neutral, washed with anhydrous ethanol for 2 to 3 times, and dried at 50 to 60° C. for 8 to 10 hours.
[0017] Preferably, in step (2), the process conditions for uniform stirring and dispersion are: stirring at 2000-3000 r / min for 12-15 minutes; the process conditions for uniform stirring and mixing are: stirring at 1500-2000 r / min for 8-10 minutes.
[0018] Preferably, in step (2), the process conditions of the pulsed magnetic field treatment are: pulsed magnetic field intensity 5-6T, pulse width 100-120ms, pulse frequency 40-50Hz, and pulse number 10-12.
[0019] Preferably, in step (3), the process conditions for stirring and mixing are: stirring at 400-500 r / min for 5-7 minutes; the process conditions for stirring evenly are: stirring at 300-400 r / min for 8-10 minutes.
[0020] A coating for building exterior walls is obtained through the above-mentioned preparation method.
[0021] Beneficial effects of the present invention:
[0022] The present invention first mixes and stirs water and a thickener, then adds a dispersant, a defoamer and a wetting agent, and continues to stir to obtain a premix; then adds modified lithium silicate, copper iron oxide, and zirconium dioxide-yttria composite microspheres to the premix, stirs and disperses evenly, continues to add silicone acrylic emulsion and acrylic emulsion, stirs and mixes, and pulses a magnetic field treatment; finally, adds a film-forming aid, a preservative, and a defoamer, stirs and mixes evenly, adds a thickener, stirs evenly, and obtains a coating for building exterior walls. The coating product has excellent temperature resistance, anti-aging, and heat insulation effects, and is suitable for use on building exterior walls.
[0023] The present invention uses silicone-acrylic emulsion and acrylic emulsion as main raw materials to ensure that the product has certain temperature resistance, aging resistance and heat insulation performance, and adds modified lithium silicate, copper iron oxide and zirconium dioxide-yttrium oxide composite microspheres to synergistically improve the coating performance.
[0024] During the preparation process, after adding silicone-acrylic emulsion and acrylic emulsion, pulse magnetic field treatment is carried out to facilitate the full mixing of the raw materials and further improve the performance of the coating. DETAILED DESCRIPTION
[0025] The present invention is further described below in conjunction with embodiments. It should be noted that the following description is only for explaining the present invention and does not limit its contents.
[0026] Embodiment 1:
[0027] A method for preparing a coating for building exterior walls, comprising the following specific steps:
[0028] (1) First, 10 kg of water and 0.8 kg of thickener were mixed and stirred, and then 1 kg of dispersant, 0.1 kg of defoamer and 0.4 kg of wetting agent were added and stirred continuously to obtain a premix;
[0029] (2) Then, 3 kg of modified lithium silicate, 5 kg of copper iron oxide, and 3 kg of zirconium dioxide-yttrium oxide composite microspheres were added to the premix, and the mixture was dispersed evenly by stirring, and 20 kg of silicone-acrylic emulsion and 25 kg of acrylic emulsion were added, and the mixture was mixed evenly by stirring, and then treated by pulse magnetic field;
[0030] (3) Finally, add 6 kg of film-forming aid, 1 kg of preservative, and 0.1 kg of defoamer, stir and mix, add 1 kg of thickener, and stir evenly to obtain the coating for exterior walls of buildings.
[0031] Among them, the thickener is hydroxyethyl cellulose; the dispersant is sodium dodecylbenzene sulfonate; the defoaming agent is HY-A10, purchased from Shanghai Huiyan New Materials Co., Ltd.; the wetting agent is glycerin; the silicone-acrylic emulsion is purchased from Shandong Xuguang Chemical Co., Ltd.; the acrylic emulsion is purchased from Shandong Chuangying Chemical Co., Ltd.; the film-forming aid is a mixture of equal amounts of ethylene glycol and dodecyl alcohol; the preservative is 5-chloro-2-methyl-4-isothiazoline-3-one.
[0032] In step (1), the process conditions for mixing and stirring are: stirring at 300 r / min for 8 minutes; the process conditions for continued stirring are: stirring at 300 r / min for 5 minutes.
[0033] In step (2), the modified lithium silicate is prepared by the following method: 10 kg of 5% lithium silicate solution is heated to 50° C., 3 kg of 3-ureapropyltriethoxysilane is added while stirring, and then 1 mol / L lithium hydroxide solution is added to adjust the pH to 11, and then 1 kg of γ-aminopropyltriethoxysilane and 1 kg of methyltriethoxysilane are added, the reaction is stirred and kept warm for 2 hours, and the mixture is naturally cooled to room temperature to obtain the modified lithium silicate.
[0034] In step (2), copper iron oxide is prepared by the following method: 1 kg CuO, 2 kg Fe2O3 and 0.2 kg polyvinyl pyrrolidone are mixed and ground for 2 hours, then calcined at 450° C. for 2 hours, and naturally cooled to room temperature.
[0035] In step (2), the zirconium dioxide-yttrium oxide composite microspheres are prepared by the following method: first, 2 kg of zirconium oxychloride and 1 kg of yttrium nitrate are dissolved in 8 kg of water to obtain an aqueous solution; then, 4 kg of polystyrene microspheres (purchased from Beijing Zhongke Keyou Technology Co., Ltd.) and 5 kg of anhydrous ethanol are added to the aqueous solution, 300W ultrasonic oscillation treatment is performed for 10 minutes, heated to 80°C, stirred at 300r / min for 8 hours, the solid is filtered out, washed with water until neutral, washed twice with anhydrous ethanol, and dried at 50°C for 8 hours.
[0036] In step (2), the process conditions for uniform stirring and dispersion are: stirring at 2000 r / min for 12 minutes; the process conditions for uniform stirring and mixing are: stirring at 1500 r / min for 8 minutes.
[0037] In step (2), the process conditions of the pulsed magnetic field treatment are: pulsed magnetic field intensity 5T, pulse width 100ms, pulse frequency 40Hz, and pulse number 10.
[0038] In step (3), the process conditions for stirring and mixing are: stirring at 400 r / min for 5 minutes; the process conditions for stirring evenly are: stirring at 300 r / min for 8 minutes.
[0039] Embodiment 2:
[0040] A method for preparing a coating for building exterior walls, comprising the following specific steps:
[0041] (1) First, 12 kg of water and 1.5 kg of thickener were mixed and stirred, and then 2 kg of dispersant, 0.15 kg of defoamer and 0.5 kg of wetting agent were added and stirred continuously to obtain a premix;
[0042] (2) Then, 5 kg of modified lithium silicate, 7 kg of copper iron oxide, and 4 kg of zirconium dioxide-yttrium oxide composite microspheres were added to the premix, and the mixture was dispersed evenly by stirring, and 25 kg of silicone-acrylic emulsion and 30 kg of acrylic emulsion were added, and the mixture was mixed evenly by stirring, and then treated by pulse magnetic field;
[0043] (3) Finally, add 8 kg of film-forming aid, 1.5 kg of preservative, and 0.15 kg of defoamer, stir and mix, add 2 kg of thickener, stir and mix evenly, and obtain the coating for building exterior walls.
[0044] Among them, the thickener is hydroxymethyl cellulose; the dispersant is fatty acid sulfonamide; the defoamer is HY-A10, purchased from Shanghai Huiyan New Materials Co., Ltd.; the wetting agent is propylene glycol; the silicone-acrylic emulsion is purchased from Shandong Xuguang Chemical Co., Ltd.; the acrylic emulsion is purchased from Shandong Chuangying Chemical Co., Ltd.; the film-forming aid is a mixture of equal amounts of ethylene glycol and dodecyl alcohol; the preservative is 1,2-benzisothiazolin-3-one.
[0045] In step (1), the process conditions for mixing and stirring are: stirring at 400 r / min for 10 minutes; the process conditions for continued stirring are: stirring at 400 r / min for 7 minutes.
[0046] In step (2), the modified lithium silicate is prepared by the following method: 10 kg of 10% lithium silicate solution is heated to 60° C., 4 kg of 3-ureapropyltriethoxysilane is added while stirring, and then 1 mol / L lithium hydroxide solution is added to adjust the pH to 12, and then 2 kg of γ-aminopropyltriethoxysilane and 2 kg of methyltriethoxysilane are added, the reaction is stirred and kept warm for 3 hours, and the mixture is naturally cooled to room temperature to obtain the modified lithium silicate.
[0047] In step (2), copper iron oxide is prepared by the following method: 1 kg CuO, 3 kg Fe2O3 and 0.25 kg polyvinyl pyrrolidone are mixed and ground for 3 hours, then calcined at 550° C. for 3 hours, and naturally cooled to room temperature.
[0048] In step (2), the zirconium dioxide-yttrium oxide composite microspheres are prepared by the following method: first, 3 kg of zirconium oxychloride and 1 kg of yttrium nitrate are dissolved in 10 kg of water to obtain an aqueous solution; then, 5 kg of polystyrene microspheres (purchased from Beijing Zhongke Keyou Technology Co., Ltd.) and 7 kg of anhydrous ethanol are added to the aqueous solution, 500 W ultrasonic oscillation treatment is performed for 15 minutes, heated to 90 ° C, stirred at 500 r / min for 10 hours, the solid is filtered out, washed with water until neutral, washed with anhydrous ethanol for 3 times, and dried at 60 ° C for 10 hours.
[0049] In step (2), the process conditions for uniform stirring and dispersion are: stirring at 3000 r / min for 15 minutes; the process conditions for uniform stirring and mixing are: stirring at 2000 r / min for 10 minutes.
[0050] In step (2), the process conditions of the pulsed magnetic field treatment are: pulsed magnetic field intensity 6T, pulse width 120ms, pulse frequency 50Hz, and number of pulses 12.
[0051] In step (3), the process conditions for stirring and mixing are: stirring at 500 r / min for 7 minutes; the process conditions for stirring evenly are: stirring at 400 r / min for 10 minutes.
[0052] Embodiment 3:
[0053] A method for preparing a coating for building exterior walls, comprising the following specific steps:
[0054] (1) First, 10 kg of water and 1.5 kg of thickener were mixed and stirred, and then 1 kg of dispersant, 0.15 kg of defoamer and 0.4 kg of wetting agent were added and stirred continuously to obtain a premix;
[0055] (2) Then, 5 kg of modified lithium silicate, 5 kg of copper iron oxide, and 4 kg of zirconium dioxide-yttrium oxide composite microspheres were added to the premix, and the mixture was dispersed evenly by stirring, and 20 kg of silicone-acrylic emulsion and 30 kg of acrylic emulsion were added, and the mixture was mixed evenly by stirring, and then treated by pulse magnetic field;
[0056] (3) Finally, add 6 kg of film-forming aid, 1.5 kg of preservative, and 0.1 kg of defoamer, stir and mix, add 2 kg of thickener, and stir evenly to obtain the coating for building exterior walls.
[0057] Among them, the thickener is carboxymethyl cellulose; the dispersant is sodium dibutylnaphthalene sulfonate; the defoaming agent is HY-A10, purchased from Shanghai Huiyan New Materials Co., Ltd.; the wetting agent is glycerin; the silicone-acrylic emulsion is purchased from Shandong Xuguang Chemical Co., Ltd.; the acrylic emulsion is purchased from Shandong Chuangying Chemical Co., Ltd.; the film-forming aid is a mixture of equal amounts of ethylene glycol and dodecyl alcohol; the preservative is 5-chloro-2-methyl-4-isothiazoline-3-one.
[0058] In step (1), the process conditions for mixing and stirring are: stirring at 300 r / min for 10 minutes; the process conditions for continued stirring are: stirring at 300 r / min for 7 minutes.
[0059] In step (2), the modified lithium silicate is prepared by the following method: 10 kg of 5% lithium silicate solution is heated to 60° C., 3 kg of 3-ureapropyltriethoxysilane is added while stirring, and then 1 mol / L lithium hydroxide solution is added to adjust the pH to 12, and then 1 kg of γ-aminopropyltriethoxysilane and 2 kg of methyltriethoxysilane are added, the reaction is stirred and kept warm for 2 hours, and the mixture is naturally cooled to room temperature to obtain the modified lithium silicate.
[0060] In step (2), copper iron oxide is prepared by the following method: 1 kg CuO, 3 kg Fe2O3 and 0.2 kg polyvinyl pyrrolidone are mixed and ground for 3 hours, then calcined at 450° C. for 3 hours, and naturally cooled to room temperature.
[0061] In step (2), the zirconium dioxide-yttrium oxide composite microspheres are prepared by the following method: first, 2 kg of zirconium oxychloride and 1 kg of yttrium nitrate are dissolved in 10 kg of water to obtain an aqueous solution; then, 4 kg of polystyrene microspheres (purchased from Beijing Zhongke Keyou Technology Co., Ltd.) and 7 kg of anhydrous ethanol are added to the aqueous solution, 300W ultrasonic oscillation treatment is performed for 15 minutes, heated to 80°C, stirred at 500r / min for 8 hours, the solid is filtered out, washed with water until neutral, washed with anhydrous ethanol for 3 times, and dried at 50°C for 10 hours.
[0062] In step (2), the process conditions for uniform stirring and dispersion are: stirring at 2000 r / min for 15 minutes; the process conditions for uniform stirring and mixing are: stirring at 1500 r / min for 10 minutes.
[0063] In step (2), the process conditions of the pulsed magnetic field treatment are: pulsed magnetic field intensity 5T, pulse width 120ms, pulse frequency 40Hz, and number of pulses 12.
[0064] In step (3), the process conditions for stirring and mixing are: stirring at 400 r / min for 7 minutes; the process conditions for stirring evenly are: stirring at 300 r / min for 10 minutes.
[0065] Embodiment 4:
[0066] A method for preparing a coating for building exterior walls, comprising the following specific steps:
[0067] (1) First, 11 kg of water and 1 kg of thickener were mixed and stirred, and then 1.5 kg of dispersant, 0.12 kg of defoamer and 0.45 kg of wetting agent were added and stirred continuously to obtain a premix;
[0068] (2) Then, 4 kg of modified lithium silicate, 6 kg of copper iron oxide, and 3.5 kg of zirconium dioxide-yttrium oxide composite microspheres were added to the premix, and the mixture was dispersed evenly by stirring, and 22 kg of silicone-acrylic emulsion and 28 kg of acrylic emulsion were added, and the mixture was mixed evenly by stirring, and then treated by pulse magnetic field;
[0069] (3) Finally, add 7 kg of film-forming aid, 1.2 kg of preservative, and 0.12 kg of defoamer, stir and mix well, add 1.5 kg of thickener, and stir well to obtain the coating for building exterior walls.
[0070] Among them, the thickener is hydroxyethyl cellulose; the dispersant is sodium dodecylbenzene sulfonate; the defoaming agent is HY-A10, purchased from Shanghai Huiyan New Materials Co., Ltd.; the wetting agent is propylene glycol; the silicone-acrylic emulsion is purchased from Shandong Xuguang Chemical Co., Ltd.; the acrylic emulsion is purchased from Shandong Chuangying Chemical Co., Ltd.; the film-forming aid is a mixture of equal amounts of ethylene glycol and dodecyl alcohol; the preservative is 5-chloro-2-methyl-4-isothiazoline-3-one.
[0071] In step (1), the process conditions for mixing and stirring are: stirring at 400 r / min for 9 minutes; the process conditions for continued stirring are: stirring at 400 r / min for 6 minutes.
[0072] In step (2), the modified lithium silicate is prepared by the following method: 10 kg of 8% lithium silicate solution is heated to 55° C., 3.5 kg of 3-ureapropyltriethoxysilane is added while stirring, and then 1 mol / L lithium hydroxide solution is added to adjust the pH to 11, and then 1.5 kg of γ-aminopropyltriethoxysilane and 1.5 kg of methyltriethoxysilane are added, the reaction is stirred and kept warm for 2 hours, and the mixture is naturally cooled to room temperature to obtain the modified lithium silicate.
[0073] In step (2), copper iron oxide is prepared by the following method: 1 kg CuO, 2.5 kg Fe2O3 and 0.22 kg polyvinyl pyrrolidone are mixed and ground for 2.5 hours, then calcined at 500° C. for 2 hours, and naturally cooled to room temperature to obtain the product.
[0074] In step (2), the zirconium dioxide-yttrium oxide composite microspheres are prepared by the following method: first, 3 kg of zirconium oxychloride and 1 kg of yttrium nitrate are dissolved in 9 kg of water to obtain an aqueous solution; then, 4.5 kg of polystyrene microspheres (purchased from Beijing Zhongke Keyou Technology Co., Ltd.) and 6 kg of anhydrous ethanol are added to the aqueous solution, 400 W ultrasonic oscillation treatment is performed for 12 minutes, heated to 85 ° C, stirred at 400 r / min for 9 hours, the solid is filtered out, washed with water until neutral, washed with anhydrous ethanol for 3 times, and dried at 55 ° C for 9 hours.
[0075] In step (2), the process conditions for uniform stirring and dispersion are: stirring at 2500 r / min for 13 minutes; the process conditions for uniform stirring and mixing are: stirring at 1800 r / min for 9 minutes.
[0076] In step (2), the process conditions of the pulsed magnetic field treatment are: pulsed magnetic field intensity 5T, pulse width 110ms, pulse frequency 45Hz, and pulse number 11.
[0077] In step (3), the process conditions for stirring and mixing are: stirring at 500 r / min for 6 minutes; the process conditions for stirring evenly are: stirring at 400 r / min for 9 minutes.
[0078] Comparative Example 1
[0079] A method for preparing a coating for building exterior walls, comprising the following specific steps:
[0080] (1) First, 10 kg of water and 0.8 kg of thickener were mixed and stirred, and then 1 kg of dispersant, 0.1 kg of defoamer and 0.4 kg of wetting agent were added and stirred continuously to obtain a premix;
[0081] (2) Then, 5 kg of copper iron oxide and 3 kg of zirconium dioxide-yttrium oxide composite microspheres were added to the premix, and the mixture was dispersed evenly by stirring, and 20 kg of silicone-acrylic emulsion and 25 kg of acrylic emulsion were added, and the mixture was mixed evenly by stirring, and then treated by pulse magnetic field;
[0082] (3) Finally, add 6 kg of film-forming aid, 1 kg of preservative, and 0.1 kg of defoamer, stir and mix, add 1 kg of thickener, and stir evenly to obtain the coating for exterior walls of buildings.
[0083] Among them, the thickener is hydroxyethyl cellulose; the dispersant is sodium dodecylbenzene sulfonate; the defoaming agent is HY-A10, purchased from Shanghai Huiyan New Materials Co., Ltd.; the wetting agent is glycerin; the silicone-acrylic emulsion is purchased from Shandong Xuguang Chemical Co., Ltd.; the acrylic emulsion is purchased from Shandong Chuangying Chemical Co., Ltd.; the film-forming aid is a mixture of equal amounts of ethylene glycol and dodecyl alcohol; the preservative is 5-chloro-2-methyl-4-isothiazoline-3-one.
[0084] In step (1), the process conditions for mixing and stirring are: stirring at 300 r / min for 8 minutes; the process conditions for continued stirring are: stirring at 300 r / min for 5 minutes.
[0085] In step (2), copper iron oxide is prepared by the following method: 1 kg CuO, 2 kg Fe2O3 and 0.2 kg polyvinyl pyrrolidone are mixed and ground for 2 hours, then calcined at 450° C. for 2 hours, and naturally cooled to room temperature.
[0086] In step (2), the zirconium dioxide-yttrium oxide composite microspheres are prepared by the following method: first, 2 kg of zirconium oxychloride and 1 kg of yttrium nitrate are dissolved in 8 kg of water to obtain an aqueous solution; then, 4 kg of polystyrene microspheres (purchased from Beijing Zhongke Keyou Technology Co., Ltd.) and 5 kg of anhydrous ethanol are added to the aqueous solution, 300W ultrasonic oscillation treatment is performed for 10 minutes, heated to 80°C, stirred at 300r / min for 8 hours, the solid is filtered out, washed with water until neutral, washed twice with anhydrous ethanol, and dried at 50°C for 8 hours.
[0087] In step (2), the process conditions for uniform stirring and dispersion are: stirring at 2000 r / min for 12 minutes; the process conditions for uniform stirring and mixing are: stirring at 1500 r / min for 8 minutes.
[0088] In step (2), the process conditions of the pulsed magnetic field treatment are: pulsed magnetic field intensity 5T, pulse width 100ms, pulse frequency 40Hz, and pulse number 10.
[0089] In step (3), the process conditions for stirring and mixing are: stirring at 400 r / min for 5 minutes; the process conditions for stirring evenly are: stirring at 300 r / min for 8 minutes.
[0090] Comparative Example 2
[0091] A method for preparing a coating for building exterior walls, comprising the following specific steps:
[0092] (1) First, 10 kg of water and 0.8 kg of thickener were mixed and stirred, and then 1 kg of dispersant, 0.1 kg of defoamer and 0.4 kg of wetting agent were added and stirred continuously to obtain a premix;
[0093] (2) Then, 3 kg of modified lithium silicate and 3 kg of zirconium dioxide-yttria composite microspheres were added to the premix, and the mixture was evenly dispersed by stirring. Then, 20 kg of silicone-acrylic emulsion and 25 kg of acrylic emulsion were added, and the mixture was evenly stirred and treated with a pulsed magnetic field.
[0094] (3) Finally, add 6 kg of film-forming aid, 1 kg of preservative, and 0.1 kg of defoamer, stir and mix, add 1 kg of thickener, and stir evenly to obtain the coating for exterior walls of buildings.
[0095] Among them, the thickener is hydroxyethyl cellulose; the dispersant is sodium dodecylbenzene sulfonate; the defoaming agent is HY-A10, purchased from Shanghai Huiyan New Materials Co., Ltd.; the wetting agent is glycerin; the silicone-acrylic emulsion is purchased from Shandong Xuguang Chemical Co., Ltd.; the acrylic emulsion is purchased from Shandong Chuangying Chemical Co., Ltd.; the film-forming aid is a mixture of equal amounts of ethylene glycol and dodecyl alcohol; the preservative is 5-chloro-2-methyl-4-isothiazoline-3-one.
[0096] In step (1), the process conditions for mixing and stirring are: stirring at 300 r / min for 8 minutes; the process conditions for continued stirring are: stirring at 300 r / min for 5 minutes.
[0097] In step (2), the modified lithium silicate is prepared by the following method: 10 kg of 5% lithium silicate solution is heated to 50° C., 3 kg of 3-ureapropyltriethoxysilane is added while stirring, and then 1 mol / L lithium hydroxide solution is added to adjust the pH to 11, and then 1 kg of γ-aminopropyltriethoxysilane and 1 kg of methyltriethoxysilane are added, the reaction is stirred and kept warm for 2 hours, and the mixture is naturally cooled to room temperature to obtain the modified lithium silicate.
[0098] In step (2), the zirconium dioxide-yttrium oxide composite microspheres are prepared by the following method: first, 2 kg of zirconium oxychloride and 1 kg of yttrium nitrate are dissolved in 8 kg of water to obtain an aqueous solution; then, 4 kg of polystyrene microspheres (purchased from Beijing Zhongke Keyou Technology Co., Ltd.) and 5 kg of anhydrous ethanol are added to the aqueous solution, 300W ultrasonic oscillation treatment is performed for 10 minutes, heated to 80°C, stirred at 300r / min for 8 hours, the solid is filtered out, washed with water until neutral, washed twice with anhydrous ethanol, and dried at 50°C for 8 hours.
[0099] In step (2), the process conditions for uniform stirring and dispersion are: stirring at 2000 r / min for 12 minutes; the process conditions for uniform stirring and mixing are: stirring at 1500 r / min for 8 minutes.
[0100] In step (2), the process conditions of the pulsed magnetic field treatment are: pulsed magnetic field intensity 5T, pulse width 100ms, pulse frequency 40Hz, and pulse number 10.
[0101] In step (3), the process conditions for stirring and mixing are: stirring at 400 r / min for 5 minutes; the process conditions for stirring evenly are: stirring at 300 r / min for 8 minutes.
[0102] Comparative Example 3
[0103] A method for preparing a coating for building exterior walls, comprising the following specific steps:
[0104] (1) First, 10 kg of water and 0.8 kg of thickener were mixed and stirred, and then 1 kg of dispersant, 0.1 kg of defoamer and 0.4 kg of wetting agent were added and stirred continuously to obtain a premix;
[0105] (2) Then, 3 kg of modified lithium silicate and 5 kg of copper iron oxide were added to the premix, and the mixture was evenly dispersed by stirring. Then, 20 kg of silicone-acrylic emulsion and 25 kg of acrylic emulsion were added, and the mixture was evenly stirred and treated with a pulsed magnetic field.
[0106] (3) Finally, add 6 kg of film-forming aid, 1 kg of preservative, and 0.1 kg of defoamer, stir and mix, add 1 kg of thickener, and stir evenly to obtain the coating for exterior walls of buildings.
[0107] Among them, the thickener is hydroxyethyl cellulose; the dispersant is sodium dodecylbenzene sulfonate; the defoaming agent is HY-A10, purchased from Shanghai Huiyan New Materials Co., Ltd.; the wetting agent is glycerin; the silicone-acrylic emulsion is purchased from Shandong Xuguang Chemical Co., Ltd.; the acrylic emulsion is purchased from Shandong Chuangying Chemical Co., Ltd.; the film-forming aid is a mixture of equal amounts of ethylene glycol and dodecyl alcohol; the preservative is 5-chloro-2-methyl-4-isothiazoline-3-one.
[0108] In step (1), the process conditions for mixing and stirring are: stirring at 300 r / min for 8 minutes; the process conditions for continued stirring are: stirring at 300 r / min for 5 minutes.
[0109] In step (2), the modified lithium silicate is prepared by the following method: 10 kg of 5% lithium silicate solution is heated to 50° C., 3 kg of 3-ureapropyltriethoxysilane is added while stirring, and then 1 mol / L lithium hydroxide solution is added to adjust the pH to 11, and then 1 kg of γ-aminopropyltriethoxysilane and 1 kg of methyltriethoxysilane are added, the reaction is stirred and kept warm for 2 hours, and the mixture is naturally cooled to room temperature to obtain the modified lithium silicate.
[0110] In step (2), copper iron oxide is prepared by the following method: 1 kg CuO, 2 kg Fe2O3 and 0.2 kg polyvinyl pyrrolidone are mixed and ground for 2 hours, then calcined at 450° C. for 2 hours, and naturally cooled to room temperature.
[0111] In step (2), the process conditions for uniform stirring and dispersion are: stirring at 2000 r / min for 12 minutes; the process conditions for uniform stirring and mixing are: stirring at 1500 r / min for 8 minutes.
[0112] In step (2), the process conditions of the pulsed magnetic field treatment are: pulsed magnetic field intensity 5T, pulse width 100ms, pulse frequency 40Hz, and pulse number 10.
[0113] In step (3), the process conditions for stirring and mixing are: stirring at 400 r / min for 5 minutes; the process conditions for stirring evenly are: stirring at 300 r / min for 8 minutes.
[0114] Test example
[0115] The temperature change resistance, aging resistance and heat insulation performance of the coatings obtained in Examples 1 to 4 and Comparative Examples 1 to 3 were tested respectively, and the specific methods are as follows:
[0116] 1. Temperature change resistance: JG / T 25-1999 "Determination of freeze-thaw cycle resistance of architectural coatings";
[0117] 2. Anti-aging: Refer to GB / T 9755-2024 "Synthetic resin emulsion exterior wall coating";
[0118] 3. Thermal insulation performance: refer to GB / T 25261-2018 "Reflective thermal insulation coatings for buildings".
[0119] The results are shown in Table 1.
[0120] Table 1. Coating performance test
[0121]
[0122] It can be seen from Table 1 that the coatings obtained in Examples 1 to 4 have excellent temperature resistance, aging resistance and heat insulation properties, and can meet the use requirements of building exterior walls.
[0123] In Comparative Example 1, the modified lithium silicate is omitted, the copper iron oxide is omitted in Comparative Example 2, and the zirconium dioxide-yttrium oxide composite microspheres are omitted in Comparative Example 3. The temperature change resistance, aging resistance and thermal insulation performance are significantly deteriorated, indicating that the modified lithium silicate, copper iron oxide and zirconium dioxide-yttrium oxide composite microspheres work synergistically to improve the temperature change resistance, aging resistance and thermal insulation performance of the coating.
[0124] Although the above describes the specific implementation methods of the present invention, it does not limit the scope of protection of the present invention. Based on the technical solution of the present invention, various modifications or variations that can be made by those skilled in the art without creative work are still within the scope of protection of the present invention.
Claims
1. A method for preparing a coating for building exterior walls, characterized in that: In parts by weight, the specific steps are as follows: (1) First, 10 to 12 parts of water and 0.8 to 1.5 parts of thickener are mixed and stirred, and then 1 to 2 parts of dispersant, 0.1 to 0.15 parts of defoamer and 0.4 to 0.5 parts of wetting agent are added, and stirring is continued to obtain a premix; (2) Then, 3 to 5 parts of modified lithium silicate, 5 to 7 parts of copper iron oxide, and 3 to 4 parts of zirconium dioxide-yttrium oxide composite microspheres are added to the premix, and the mixture is evenly dispersed by stirring, and 20 to 25 parts of silicone-acrylic emulsion and 25 to 30 parts of acrylic emulsion are added, and the mixture is evenly stirred and treated with a pulsed magnetic field; (3) Finally, add 6 to 8 parts of film-forming aid, 1 to 1.5 parts of preservative, and 0.1 to 0.15 parts of defoamer, stir and mix, add 1 to 2 parts of thickener, stir and mix, and the coating for building exterior walls is obtained.
2. The preparation method according to claim 1, characterized in that: The thickener is selected from hydroxyethyl cellulose, hydroxymethyl cellulose or carboxymethyl cellulose; the dispersant is selected from sodium dodecylbenzene sulfonate, fatty acid sulfonylamide or sodium dibutylnaphthalene sulfonate; the defoamer is a mineral oil defoamer; the wetting agent is selected from glycerol or propylene glycol; the film-forming aid is obtained by mixing ethylene glycol and dodecyl alcohol in equal amounts; and the preservative is selected from 5-chloro-2-methyl-4-isothiazoline-3-one or 1,2-benzisothiazolin-3-one.
3. The preparation method according to claim 1, characterized in that: In step (1), the process conditions for mixing and stirring are: stirring at 300-400 r / min for 8-10 minutes; the process conditions for continued stirring are: stirring at 300-400 r / min for 5-7 minutes.
4. The preparation method according to claim 1, characterized in that: In step (2), the modified lithium silicate is prepared by the following method, measured in parts by weight: 10 parts of a 5-10% lithium silicate solution is heated to 50-60° C., 3-4 parts of 3-ureapropyltriethoxysilane are added while stirring, and then 1 mol / L lithium hydroxide solution is added to adjust the pH to 11-12, and then 1-2 parts of γ-aminopropyltriethoxysilane and 1-2 parts of methyltriethoxysilane are added, the reaction is stirred and kept warm for 2-3 hours, and the mixture is naturally cooled to room temperature to obtain the modified lithium silicate.
5. The preparation method according to claim 1, characterized in that: In step (2), the copper iron oxide is prepared by the following method, in parts by weight: 1 part of CuO, 2 to 3 parts of Fe2O3 and 0.2 to 0.25 parts of polyvinyl pyrrolidone are mixed and ground for 2 to 3 hours, then calcined at 450 to 550° C. for 2 to 3 hours, and naturally cooled to room temperature to obtain the copper iron oxide.
6. The preparation method according to claim 1, characterized in that: In step (2), the zirconium dioxide-yttrium oxide composite microspheres are prepared by the following method, measured in parts by weight: first, 2 to 3 parts of zirconium oxychloride and 1 part of yttrium nitrate are dissolved in 8 to 10 parts of water to obtain an aqueous solution; then, 4 to 5 parts of polystyrene microspheres (purchased from Beijing Zhongke Keyou Technology Co., Ltd.) and 5 to 7 parts of anhydrous ethanol are added to the aqueous solution, ultrasonically vibrated at 300 to 500W for 10 to 15 minutes, heated to 80 to 90°C, stirred at 300 to 500r / min for 8 to 10 hours, filtered to obtain the solid, washed with water until neutral, washed with anhydrous ethanol for 2 to 3 times, and dried at 50 to 60°C for 8 to 10 hours.
7. The preparation method according to claim 1, characterized in that: In step (2), the process conditions for uniform stirring and dispersion are: stirring at 2000-3000 r / min for 12-15 minutes; the process conditions for uniform stirring and mixing are: stirring at 1500-2000 r / min for 8-10 minutes.
8. The preparation method according to claim 1, characterized in that: In step (2), the process conditions of the pulse magnetic field treatment are: pulse magnetic field intensity 5-6T, pulse width 100-120ms, pulse frequency 40-50Hz, and pulse number 10-12.
9. The preparation method according to claim 1, characterized in that: In step (3), the process conditions for stirring and mixing are: stirring at 400-500 r / min for 5-7 minutes; the process conditions for stirring evenly are: stirring at 300-400 r / min for 8-10 minutes.
10. A coating for building exterior walls, characterized in that: The invention is obtained by the preparation method according to any one of claims 1 to 9.